2017
DOI: 10.1111/scd.12224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion in individuals with and without intellectual disability: A comparative study

Abstract: In this study, the prevalence of malocclusion was found to be higher and more severe in intellectual disabled participants. The dental practitioner should understand the particular relevance of this problem especially in patients with intellectual disabilities where impaired oral functions and poor appearance may further complicate oral health and increase negative social responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
2
7
1
4
Order By: Relevance
“…There are only a few studies using DAI for occlusion evaluation. Cabrita et al 24 found a DAI value on people with ID of 32.80, similar to the value observed in this group of individuals with FXS. Note that 45.2% presented a mandatory need of treatment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…There are only a few studies using DAI for occlusion evaluation. Cabrita et al 24 found a DAI value on people with ID of 32.80, similar to the value observed in this group of individuals with FXS. Note that 45.2% presented a mandatory need of treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Note that 45.2% presented a mandatory need of treatment. This value was higher than the one found in the ID study (18.8%) 24 . This fact may be due to the FXS specific characteristics.…”
Section: Discussioncontrasting
confidence: 80%
“…A further caveat requiring discussion is the lack of inclusion of confounding factors amongst articles. There are a multitude of variables that influence oral health: from simple physical ability to complete oral hygiene (Gallagher & Scambler ), malocclusion (Cabrita, Bizarra, & Graça ) or dental trauma from epileptic seizures (Aragon & Burneo ) to the more complex influence of medication (Ciancio ) or systemic diseases. People taking 5+ medications (polypharmacy) are at an increased risk of poor oral health due to anticholinergic burden causing xerostomia (dry mouth) leading to an increased risk of dental caries (Scottish Government Model of Care Polypharmacy Working Group ; Vázquez, Garcillan, Rioboo, & Bratos ).…”
Section: Discussionmentioning
confidence: 99%
“…Maxillar and anterior teeth protrusion, deep overbite, mandibular grows with clockwise rotation, incompetent growth of lip, poor morphology of chin and other poor coordinated surface types are clinical manifestations with Angle class II division 1 malocclusion patients (Cabrita et al, 2017;Mehta et al, 2017;Ozbilek et al, 2017). These performances affect patients' confidence, mental health and daily communication.…”
Section: Introductionmentioning
confidence: 99%